Development of a Single-Session, Transdiagnostic Preventive Intervention for Young Adults at Risk for Emotional Disorders. Issue 5 (September 2018) - Bentley, Kate H.; Boettcher, Hannah; Bullis, Jacqueline R.; Carl, Jenna R.; Conklin, Laren R.; Sauer-Zavala, Shannon; Pierre-Louis, Catherine; Farchione, Todd J.; Barlow, David H.
Cognitive-behavioral prevention programs have demonstrated efficacy in reducing subclinical symptoms of anxiety and depression, and there is some evidence to suggest that they can lower the risk of future disorder onset. However, existing interventions tend to be relatively lengthy and target specific disorders or problem areas, both of which limit their potential for widespread dissemination. To address these limitations, we aimed to develop a single-session, transdiagnostic preventive intervention based on the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders for young adults at risk for developing anxiety and/or depressive disorders within a college setting. Results from this proof-of-concept study indicated that the intervention was viewed as highly satisfactory and acceptable. The intervention also was successful at delivering adaptive emotion management skills in its 2-hr workshop format. Future studies evaluating the efficacy of this novel transdiagnostic, emotion-focused prevention program are warranted.